Smart specialization strategies at national, regional, or local levels? Synergy and policy-making in German systems of innovation - Henriette Ruhrmann; Michael Fritsch; Loet Leydesdorff (Friedrich Schiller University Jena, 2020)
Employing a quantitative, data-driven tool - the Triple Helix Indicator - to microdata of firms in Germany, we develop an evidence base for innovation-policy strategies. We aim to answer the question which level of government (local, regional, national) might be most effective for strategic innovation policy-making based on smart specialization in Germany. The empirical results show that the country is decentralized to the extent that it cannot be considered a "national" innovation system. More than two-thirds of innovation-system synergy is generated at the lower levels of districts (NUTS3) and Governmental Regions (NUTS2). In high-tech and medium-tech manufacturing, former East and West Germany, as well as North and South Germany, can be considered separate sub-national innovation systems. These findings strengthen the case for region- and context-specific innovation policies. The results illustrate the value of the Triple Helix Indicator for systematic regional mapping and serve as evidence for policy-makers to expand RIS3 policy strategies to the regional and local level in Germany.
Keywords: O30; R11; O38; O52; 330; Innovation systems; Triple Helix; Germany; Redundancy; Synergy